The Long Road from Neoliberalism to Neopopulism in ECE: The social paradox of neopopulism and decline of the Left - Ágh, Attila (Baltic Journal of Political Science, 2018)
[full article and abstract in English]We live in a “post-neoliberal world”, as it has been discussed in the mainstream literature, but the vital link between neoliberalism and neopopulism has been rarely discussed. Nowadays in international political science it is very fashionable to criticise the long neoliberal period of the last decades, still its effect on the rise of neopopulism has not yet been properly elaborated. To dig deeper into social background of neopopulism, this paper describes the system of neoliberalism in its three major social subsystems, in the socio-economic, legal-political and cultural-civilizational fields. The historical context situates the dominant period of neoliberalism between the 1970s in the Old World Order (OWO) and in the 2010s in the New World Order (NWO). In general, neoliberalism’s cumulative effects of increasing inequality has produced the current global wave of neopopulism that will be analysed in this paper in its ECE regional version. The neopopulist social paradox is that not only the privileged strata, but also the poorest part of ECE’s societies supports the hard populist elites. Due to the general desecuritization in ECE, the poor have become state dependent for social security, yet paradoxically they vote for their oppressors, widening the social base of this competitive authoritarianism. Thus, the twins of neoliberalism and neopopulism, in their close connections—the main topic of this paper—have produced a “cultural backlash” in ECE along with identity politics, which is high on the political agenda.
Keywords: New World Order; nature of neoliberalism; post-neoliberal world; desecuritization and nativist identity politics